Sinkronisasi Pangkalan Data Rumah Sakit dengan Aplikasi Open Source SymmetricDS - Andi Wahju Rahardjo Emanuel; Teresa Liliana Wargasetia; Ade Kurnia Surawijaya (Maranatha University Press, 2017)
Health is an important supporting factor in the society. One of the curative implementation of the healthcare is hospital. Supporting system based on Information Technology of hospital is called Hospital Information System (SIRS) in which this system is mandatory in every hospital. Unfortunately, this system is developed individually by the hospital so that the integration of the system in higher levels is difficult. This research demonstrates integration of Hospital Information System in small scale using SymmetricDS Open Source database replication software. It can be shown that the integration of Hospital Information System is highly possible to enable higher scale healthcare support system in the future.